Análisis de las tecnologías SAAS y los Frameworks para un sistema transaccional de ventas online para la empresa el bosque de la ciudad de Babahoyo. - Aguirre Mora, Heydi Alejandra (2022)
Today, companies are looking to automate their processes. This means the ability of technology to perform many of the tasks that humans perform daily at their workstation. This automated function also controls; modifies and clarifies the operational nature of work and activities. Digital technologies have grown exponentially, and their use has become globalized. The naturist center "El Bosque" is located on Avenida 10 de Agosto and Eloy Alfaro in the city of Babahoyo. It is characterized by selling organic products of excellent quality such as: Nutri-calm, Ulcerax, Omega 3, Vegetable Charcoal, with the aim of providing optimal service and trying to improve the quality of life of all people in relation to their health and how to take care of themselves nutritionally through natural medicine. With the information obtained about the SaaS technologies and its Frameworks, it was possible to identify that it is a tool that will help to improve the performance of the transactional system with a greater storage capacity, in addition to optimize technical processes, and an integration to the system which means that the user does not have to do anything, in such a way, that can offer the company a solution to the problems of performance, cost, time through this software as a service. Finally, it should be noted that the result of the analysis of the corresponding information provided a lot of very important data determining that it is feasible to implement SaaS technology in the transactional system as this tool will improve processes and increase its advantages giving the company a competitive advantage in the market.